2020
DOI: 10.1136/archdischild-2019-318284
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent mental health of NICU graduates: an observational study

Abstract: ObjectiveTo investigate the mental health of children and adolescents admitted to neonatal intensive/special care units (NICUs) in infancy.MethodsThis cross-sectional study used a provincially representative cohort from the 2014 Ontario Child Health Study. Parents provided data on psychiatric disorders using the MINI International Neuropsychiatric Interview for Children and Adolescents in 3141 children aged 4–11 years (NICU n=389; control n=2752) and in 2379 children aged 12–17 years (NICU n=298; control n=208… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Neonatal ICU (NICU) and pediatric ICU (PICU) survivors have been found to suffer from common psychiatric disorders, including depression, anxiety and post-ICU syndromes [5,6,13,14], and from new or increasing impairments in various cognitive functions [6][7][8]. Major identified risk factors which account for these impairments are both the critical illness itself in addition to elements related to hospitalization in and of itself.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal ICU (NICU) and pediatric ICU (PICU) survivors have been found to suffer from common psychiatric disorders, including depression, anxiety and post-ICU syndromes [5,6,13,14], and from new or increasing impairments in various cognitive functions [6][7][8]. Major identified risk factors which account for these impairments are both the critical illness itself in addition to elements related to hospitalization in and of itself.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study showed that preterm children with BPD are at particular risk for poor academic outcome, which, among others, may be due to the fact that the BPD frequency is increasing among neonates with extremely low BW and GA [30]. Preterm infants are more likely to show behavioural and psychologi-cal problems compared to full-term babies [31]. These children more often develop attention deficit hyperactivity disorder (ADHD), autism spectrum disorder, emotional and conduct problems (including anxiety and depression) or difficulties in contacts with peers.…”
Section: Neurodevelopmental Outcomementioning
confidence: 95%
“…No register studies examined specific anxiety disorders separately. One small cohort study found that treatment in a neonatal intensive care unit (NICU) was associated with specific phobias ( 19 ) and two identified it to associate with separation anxiety disorders ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%